PERBANDINGAN STRUKTUR CERITA RAKYAT LEGENDA BUJANG SAMBILAN DI NAGARI PANINGGAHAN KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK DENGAN STRUKTUR CERITA RAKYAT LEGENDA BUJANG SAMBILAN DI PASA AKAIK KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Tanhas, Iis Meli Witari Aslin; Hayati, Yenni; Nst., Muhammad Ismail (Universitas Negeri Padang, 2017)
The purpose of this study were (1) to describe the structure of legends folklore Single Part of Nagari Paninggahan; (2) describe the structure of legends folklore Single Part of Pasa Akaik; (3) describe the structure of comparative folklore legends Single Part of Nagari Paninggahan the structure of legends Single Part in Pasa Akaik. This study is a qualitative research method. This study found that the ratio of the two legends found differences in flow elements, background elements, and elements of the theme. For the second equation legendary figure found expression in Single Part. Characterizations Single Part as nine young men who became the antagonist. Then at the end of the story is equally doomed to fish.Keywords:Â folklore, comparative, structure of plot